Kampung Transmigrasi dan Kontruksi Kerukunan Umat Beragama; Mamasa Sebagai Wilayah Pasca Konflik - Muhammad Arsyam; Zakirah Zakirah; Sulaiman Ibrahim (Al-Ulum, 2021)
The focus of this research is finding the construction of religious harmony in former conflict areas in Indonesia. The aim is to photograph the process of resolving religious conflicts in Kampung Rano in Mamasa of West Sulawesi Province. This research uses a qualitative method using a phenomenological approach by collecting socio-religious data and interviews from researchers with objects. This study empirically shows that finds the importance of understanding the value of pluralism has been taking place, especially for the people of Kampung Rano to regenerate an economic situation that has been devastated for more than a decade. On the other hand, there are a number of agreements between the transmigrant community and local residents, one of which is to no longer use religious attributes and symbols in political activities.